Profitability Ratios on Capital and Investment Analysis of Ukrainian Hospitality Industry (calculated by official statistical reporting) - Chaika, Tetiana (Klaipeda University, 2019)
Profitability is a characteristic of the ability of a company to generate profits per unit of revenue (income), assets, capital, investments, cash flows, etc. Single isolated values of return on capital (investment) are not able to provide information about the success or failure of the use of capital and investments. This study presents the main metrics of return on capital and investment and the method of their calculation on the Ukrainian companies’ open financial statements.

Рентабельність – характеристика здатності підприємства генерувати прибуток у розрахунку на одиницю виручки (доходу), активів, капіталів, інвестицій, грошових потоків тощо. Поодинокі ізольовані значення рентабельності капіталу і інвестицій не здатні надати інформацію про успішність чи неуспішність використання капіталу і інвестицій. В даному дослідженні наведені основні метрики рентабельності капіталу і інвестицій і методика їх розрахунку по відкритій фінансової звітності українських підприємств.
Аналіз рентабельності капіталу і інвестицій українських підприємств сфери гостинності (розрахунок по офіційної статистичної звітності)
Keywords: profitability; return on equity; return on investment; return on capital employd; return on total capital; equity; long-term debts; рентабельність; рентабельність власного капіталу; рентабельність інвестицій; рентабельність задіяного капіталу; рентабельність капіталу; власний капітал; позиковий капітал